Marosok Dalam Perspektif Desain Media: Kajian Komunikasi Visual Pada Tradisi Transaksi Tradisional Minangkabau - Lilian Lilian; Immanuel Immanuel; Hasan Basri Durin; Muhammad Rizki (Jurnal Sosial Humaniora dan Pendidikan, 2026)
This study examines the marosok tradition of the Minangkabau community as a form of nonverbal communication through the lens of media design, focusing on its visual communication structure and potential transformation into contemporary media practices. Employing a qualitative descriptive approach with a visual ethnography paradigm, data were collected through participatory observation, in-depth interviews, and visual documentation in a livestock market setting. The findings reveal that marosok operates as a structured system of tactile-kinetic signs, where finger gestures, pressure, and concealed interaction within cloth function as symbolic codes representing numerical values and negotiation agreements. This system demonstrates consistency, efficiency, and simplicity, aligning with core principles of visual communication design. Beyond its economic function, marosok embodies ethical values such as trust, discretion, and mutual understanding, which are embedded within its symbolic interactions. The study further argues that these culturally grounded visual elements can be translated into modern media design frameworks, including interactive and user-centered design contexts. By integrating local wisdom into design practices, this research contributes to the development of culturally responsive visual communication models that reinforce identity while maintaining relevance in digital environments